2017
DOI: 10.1136/bmjopen-2017-018285
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal diagnosis on survival of newborns with four congenital heart defects: a prospective, population-based cohort study in France (the EPICARD Study)

Abstract: Objectives(1) Assess the population-level probability of prenatal diagnosis and termination of pregnancy for fetal anomaly for four major congenital heart defects; (2) Examine, using population-based data, the relation between timing of (prenatal vs postnatal) diagnosis and risk of infant (ie, < 1 year) mortality for four major congenital heart defects (CHDs).DesignPopulation-based cohort (the EPIdémiologie des CARDiopathies congénitales) study.SettingGreater Paris area (Paris and its surrounding suburbs).Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 21 publications
6
52
0
1
Order By: Relevance
“…Despite increased awareness and education, prenatal detection of various forms of CHD remains low, with outflow tract anomalies historically lower than for other types of critical CHD (such as single ventricle lesions) . Contemporary studies have shown a wide range of prenatal diagnosis rates for conotruncal anomalies (Table ) . Many outflow tract anomalies can appear normal when visualizing only the four‐chamber view (Figure A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increased awareness and education, prenatal detection of various forms of CHD remains low, with outflow tract anomalies historically lower than for other types of critical CHD (such as single ventricle lesions) . Contemporary studies have shown a wide range of prenatal diagnosis rates for conotruncal anomalies (Table ) . Many outflow tract anomalies can appear normal when visualizing only the four‐chamber view (Figure A).…”
Section: Discussionmentioning
confidence: 99%
“…20 Contemporary studies have shown a wide range of prenatal diagnosis rates for conotruncal anomalies ( Table 5). [21][22][23][24][25][26][27][28] Many outflow tract anomalies can appear normal when visualizing only the four-chamber view ( Figure 1A). The ability of obstetric anatomic ultrasound to identify outflow tract anomalies increases substantially when ventricular outflow tract imaging supplements the more traditional four-chamber view.…”
Section: Pre-guidelines Vs Post-guidelinesmentioning
confidence: 99%
“…Coarctation of the aorta (CoA) remains a challenging diagnosis to make before birth [1][2][3][4][5]. Unlike other cardiac malformations in which abnormal anatomy may be DeVore/Jone/Satou/Sklansky/Cuneo Fetal Diagn Ther 2020;47:429-439 430 DOI: 10.1159/000500022 present as early as the 1st trimester (e.g., mitral atresia, truncus arteriosus, aortic and pulmonary atresia, transposition of the great arteries, and tetralogy of Fallot), CoA often presents in the 2nd and 3rd trimesters of pregnancy and manifests as ventricular size disproportion (right ventricle [RV] > left ventricle [LV]) [3][4][5][6]. However, the false-positive rate for detecting fetuses with CoA has been as high as 65% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have provided different results on the benefi cial effects of fetal diagnostics on morbidity and mortality in newborns and children. 4,[42][43][44] The authors of this work consider the prenatal care system to be very effective in the Czech Republic. It is essential to have complete information on pathological pregnancies to provide the affected family with proper counseling and fetal transport "in utero" for delivery to an adequate workplace.…”
Section: (4) 232mentioning
confidence: 99%